2017
DOI: 10.1136/sextrans-2016-052974
|View full text |Cite
|
Sign up to set email alerts
|

Traditional healers, faith healers and medical practitioners: the contribution of medical pluralism to bottlenecks along the cascade of care for HIV/AIDS in Eastern and Southern Africa

Abstract: ObjectivesThere are concerns that medical pluralism may delay patients’ progression through the HIV cascade-of-care. However, the pathways of impact through which medical pluralism influence the care of people living with HIV (PLHIV) in African settings remain unclear. We sought to establish the manifestation of medical pluralism among PLHIV, and explore mechanisms through which medical pluralism contributes bottlenecks along the HIV care cascade.MethodsWe conducted a multicountry exploratory qualitative study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
86
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 27 publications
2
86
0
1
Order By: Relevance
“…22,14,60 Various participants described healthcare providers as disapproving and rude and they also felt mistreated by them. A study by Govender et al 14 In South Africa, attention has recently focused on the concept of medical pluralism 70 which occurs when individuals utilise more than one medical system when seeking healthcare. 70 Such healthcare systems include traditional and faith-based systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,14,60 Various participants described healthcare providers as disapproving and rude and they also felt mistreated by them. A study by Govender et al 14 In South Africa, attention has recently focused on the concept of medical pluralism 70 which occurs when individuals utilise more than one medical system when seeking healthcare. 70 Such healthcare systems include traditional and faith-based systems.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Govender et al 14 In South Africa, attention has recently focused on the concept of medical pluralism 70 which occurs when individuals utilise more than one medical system when seeking healthcare. 70 Such healthcare systems include traditional and faith-based systems. It was evident in this study that many participants had been consulting traditional healers and using or contemplated using traditional medication.…”
Section: Discussionmentioning
confidence: 99%
“…They "provide health care by using plant, animal and mineral substances, and other methods based on social, cultural, and religious practices" [12]. Prior work in medically pluralistic contexts shows that initial choice of therapeutic modality is driven by patients' perceived etiology of illness, and provider trustworthiness [13][14][15][16]. Patients may switch modalities in the setting of treatment "failure", when symptoms worsen or persist despite treatment [13,17].…”
Section: Introductionmentioning
confidence: 99%
“…Medical pluralism has been characterized as a central factor contributing to poor health outcomes. For example, researchers have shown that use of traditional medicine delays HIV testing and ART initiation [18], and interrupts HIV treatment [13], for people living with HIV (PLHIV) . In Mozambique, PLHIV initially seeking care from traditional healers experienced significantly longer delays to diagnosis compared with those who did not utilize healers; this delay exponentially increased with corresponding increases in the number of healers consulted prior to receiving HIV testing [18].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 15 years, there has been a steady flow of peer reviewed reports relating to the unintended health-related consequences associated with medical pluralism in eastern and southern Africa. In the context of HIV, medical pluralism is primarily associated with delays in testing and treatment interruption (for one of many examples, see Moshabela et al 2017).…”
Section: Introductionmentioning
confidence: 99%